Nitrogen contributions from decomposing cover crop residues to maize in a tropical derived savanna - Sanginga, P.; Vanlauwe, Bernard; Merckx, Roel; Ibewiro, B. (2000)
In cover cropping systems in the tropics with herbaceous legumes, plant residues are expected to supply nitrogen (N) to non-legume crops during decomposition. Field experiments were carried out to (i) determine the effects of residue quality on decomposition and N release patterns of selected plants in cover cropping systems, (ii) relate the pattern of residue N release to N uptake by maize in cover cropping systems. To study decomposition, litter bags were used and monitored over two maize growing seasons. The residues studied were mucuna (Mucuna pruriens (L.) DC. var. utilis (Wright) Bruck), lablab (Lablab purpureus (L.) Sweet), and leaves and rhizomes of imperata (Imperata cylindrica (L.) Raueschel). Mucuna and lablab decomposed rapidly losing more than 60% of their dry weight within 28 days. In contrast, imperata decomposed slowly with only 25% of its dry matter lost in 56 days. At 28 days, mucuna had released 154 kg N ha-1 in in-situ mulch systems and 87 kg N ha-1 in live- mulch systems representing more than 50% of its N. More than 64% of N in lablab was released within 28 days amounting to 21 to 174 kg N ha-1. Imperata rhizomes mineralized 4 to 14 kg N ha-1 within 14 days, and subsequently immobilized N until 112 days whereas imperata leaves immobilized N throughout the study period. Decomposition and N release rates from the plant residues were most strongly correlated with the (lignin+polyphenol)/N ratio, N content, lignin/N ratio, polyphenol/N ratio, C/N ratio and lignin content of the residues. Relative to the controls, herbaceous legume residues increased maize dry matter yield and N uptake during the two cropping seasons. At 84 days, the maize crop had utilized 13 to 63 kg N ha-1from mucuna representing 13 to 36% of N released, whereas 16 to 25% of N released from mucuna was recovered by the maize crop at 168 days. The first maize crop recovered 9 to 62 kg N ha-1 or 28 to 35% of N released from lablab. However, at 168 days, N uptake by maize in antecedent live-mulched lablab was 32% higher than the quantity of N released, whereas imperata residues generally, resulted in net reduction of maize N uptake.